Hit and go CAS9 delivered through a lentiviral based self-limiting circuit - Gianluca Petris (Nature Portfolio, 2017)
While CRISPR-Cas9 is a powerful technology, it’sin vivoapplication can be limited by unwanted off-target editing events. Here the authors present SLiCES, a self-limiting Cas9 circuit to enhance editing by preventing residual nuclease activity.